NEEDS ANALYSIS: DEVELOPING AN ESP SPEAKING MOOC MODEL IN HIGER EDUCATION CONTEXT - Soraya, Kiky; Lengkanawati, Nenden Sri; Purnawarman, Pupung (English Review: Journal of English Education, 2024)
This study aims to investigate the needs and learning requirements of English for Specific Purposes (ESP) students in the context of developing a Massive Open Online Course (MOOC) model for ESP speaking skills. The research employed a qualitative approach, utilizing Comprehensive Needs Analysis (CNA) techniques. Data was collected through document analysis, Forum Group Discussions (FGDs) with students, interviews with lecturers, and meetings with experts. Data analysis followed qualitative methodologies, including data reduction, display, and conclusion drawing. The study reveals significant insights into students' backgrounds, English proficiency levels, and experiences with MOOCs. Participants primarily perceive their English proficiency as intermediate. While MOOCs are viewed as valuable supplementary resources, students desire more diversity and interactivity in their online learning experiences. Furthermore, the research highlights students' desires for comprehensive speaking skills development, integrated learning experiences, supportive learning environments, and user-friendly technology platforms. This study fills a gap in the literature by investigating the specific needs and learning requirements of ESP students for developing an ESP Speaking MOOC model, particularly in Indonesian context. The findings suggest the importance of prioritizing speaking skills, integrating various language skills, fostering supportive learning environments, and leveraging user-friendly technology platforms in the development of ESP Speaking MOOC models. Addressing these needs is crucial for maximizing learning outcomes and student engagement in online language learning environments.